THE INFLUENCE OF PERSONALITY AND ORGANIZATIONAL COMMITMENT AND WORK ENGAGEMENT TO EMPLOYEE SATISFACTION AND EMPLOYEE PERFORMANCE DPRD SAMARINDA CITY - Fakhruddin, Fuad; Ilmi, Zainal; Achmad, Gusti Noorlitaria (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
In this study involving Civil Servants in Samarinda City DPRD. In this study, to see the performance of employees used a sample of 82 respondents. The data analysis used by the author is the Structural Equation Model (SEM). Hypothesis testing is done by multivariate analysis carried out through the SmartPLS program. Data analysis through partial Least Square (PLS) is done through two stages, namely: First, Assessing the outer model or measurement model. Second, assess the inner model or structural model. The results showed that Personality had a positive influence on employee job satisfaction, organizational commitment had a positive influence on employee job satisfaction, work engagement gave a positive effect on satisfaction, Personality had a positive influence on employee performance, organizational commitment had a positive influence on employee performance, work engagement provide a positive influence on employee performance, job satisfaction has a positive influence on the performance of employees of the Samarinda City Regional Representative Council. Keywords: Personality, Organizational Commitment, Work Engagement, Job Satisfaction, Employee Performance